The Effect of Work Discipline and Workload on Employee Performance Moderated by Civil Apparatus Performance Allowances at the West Nusa Tenggara Natural Resource Conservation Center - Susanty; Mukmin Suryatni; Siti Nurmayanti (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the influence of work discipline and workload on employee performance, as well as to examine the role of performance allowances as a moderating variable at the West Nusa Tenggara Natural Resources Conservation Center (BKSDA NTB). The study used a quantitative approach with a causal design. The research sample consisted of 78 employees determined by saturated sampling technique. Data were collected through questionnaires and analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results showed that work discipline had a positive and significant effect on employee performance, indicating that compliance with rules, regular attendance, and work responsibilities consistently improve employee performance. Conversely, workload had a negative and significant effect on performance, indicating that excessive task demands can reduce employee effectiveness and performance. Further findings revealed that performance allowances moderated the effect of work discipline on performance, thus increasing allowances strengthened the positive impact of discipline. Furthermore, performance allowances moderated the effect of workload on performance, indicating that adequate and fair allowances can mitigate the negative effects of high workloads. Theoretically, this study enriches the literature on factors influencing employee performance, particularly the role of performance allowances as a moderating variable. Practically, the research findings can serve as a basis for the NTB BKSDA in formulating policies to improve discipline, manage workload, and implement more effective and equitable performance allowance mechanisms.